A study on the relationship between employee benefits and employee work productivity at Majlis Ugama Islam dan Adat Resam Melayu Pahang, Pekan / Hafshah Labilah Abdul Hamid - Abdul Hamid, Hafshah Labilah (Faculty of Business and Management, 2018)
Employee benefits or welfare can be defined as a corporate attitude or duty reflected in the communicated watch over worker at all measures, supporting their work and the earth in which it is performed. Most of the companying usually see the employee benefits as important for their employees but they do not know the most important one. The goal of studying about employee benefits are to know what are the most preferred benefits and which benefit give more impact on employee work productivity in Majlis Ugama Islam Dan Adat Resam Melayu Pahang, Pekan. The objective of this study are to identify the type of employee's benefits that employees need the most and to determine the relationship between employee's benefits and employees' productivity. Besides that, the significant of the study will give influence and benefits to organization or employer and also employees of the organization. But in this study still have limitation which is the result of the study cannot be generalized to all organizations. Furthermore, the elements involved in benefit dimensions were limited to only three elements that are day care service, provide counselling sessions and employees' training opportunities, although there are many factors that could be considered in the benefit dimensions. Benefits that employees consider available in this company are bonus or allowance, medical panel, and opportunity for training. The result shown that the benefits that employees needed most but organization not provided is child care. These benefit is considered important for them in enhancing their work productivity.